Coated fuel cell catalyst material
Patent Information
- Application Number
- JP2022024508
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-02-22
- Filing Date
- 2022-02-21
- Publication Date
- 2026-10-22
- Estimated Expiration
- 2042-02-21
Smart Images

Figure 0007939768000002 
Figure 0007939768000003 
Figure 0007939768000004
Abstract
Description
[Technical Field]
[0001] This disclosure relates to coated fuel cell catalyst materials, for example, fuel cell catalyst materials coated with a defective carbon-based layer. [Background technology]
[0002] Fuel cells have shown promise as an alternative power source for vehicles and other transportation applications. Fuel cells operate using renewable energy carriers, such as hydrogen. They also operate without harmful emissions or greenhouse gases. However, fuel cell technology has limited adoption due to the relatively high cost of materials within the fuel cell stack. One material that significantly contributes to the overall cost of a fuel cell stack is the catalyst material, such as platinum catalysts. Catalyst materials are present in the catalyst layers of both the anode and cathode of the fuel cell. The durability of the catalyst material impacts the overall cost of fuel cell technology. [Overview of the project] [Means for solving the problem]
[0003] According to one embodiment, a catalyst material for a fuel cell is disclosed. The catalyst material for the fuel cell may comprise metal catalyst particles formed of a metallic material and a carbon-based coating composition that at least partially coats at least some of the metal catalyst particles. The carbon-based coating composition may comprise a carbon network. The carbon-based coating composition can be doped with a dopant. The carbon-based coating composition may comprise several defects formed by one or more carbon atom vacancies in the carbon network. The carbon-based coating composition may be made from non-aromatic carbon molecules.
[0004] According to other embodiments, a catalytic electrode for a fuel cell is disclosed. The catalytic electrode for the fuel cell may include a catalyst support and a catalytic material supported on the catalyst support. The catalytic material may include metal catalyst particles formed of a metallic material and a carbon-based coating composition that at least partially coats at least some of the metal catalyst particles. The carbon-based coating composition may include a carbon network. The carbon-based coating composition can be doped with a dopant. The carbon-based coating composition may include several defects formed by one or more carbon atom vacancies in the carbon network. The carbon-based coating composition may be made from non-aromatic carbon molecules.
[0005] Further embodiments disclose a method for producing a catalyst material for a fuel cell. The method may include reacting a metal salt of a metal-containing precursor with carbon molecules of the precursor to form a catalyst material comprising metal catalyst particles and a carbon-based coating composition that at least partially coats at least some of the metal catalyst particles. The carbon molecules of the precursor may be non-aromatic. [Brief explanation of the drawing]
[0006] [Figure 1] Figure 1 shows a schematic side view of a fuel cell. [Figure 2] Figure 2 is a schematic diagram of a computing platform available for implementing the algorithms, calculations, and / or methods of density functional theory (DFT) and / or abu inicio molecular dynamics (AIMD) in one or more embodiments. [Figure 3] Figure 3 is a schematic diagram illustrating the formation of a Pt-C bond from an AIMD simulation of the chemical reaction between Pt hydrate salt in water and aniline after an annealing process under an inert N2 atmosphere. [Figure 4] Figure 4 is a schematic diagram of a fuel cell catalyst material having a defective carbon-based coating according to one embodiment. [Figure 5]Figures 5A to 5C are schematic diagrams showing the chemical interfaces between a pure graphene sheet and Pt atoms, between an N-doped graphene sheet and Pt atoms, and between a B-doped graphene sheet and Pt atoms, respectively. [Figure 6] Figures 6A and 6B are schematic diagrams of isosurface plots of simulated electron density differences at the chemical interface between a B-doped graphene sheet and Pt atoms, and between a N-doped graphene sheet and Pt atoms, respectively. [Modes for carrying out the invention]
[0007] Detailed explanation Embodiments of the present disclosure are described herein. However, it should be understood that the disclosed embodiments are merely examples, and other embodiments may take various and alternative forms. The drawings are not necessarily to scale, and some features may be exaggerated or minimized to illustrate the details of elements. Accordingly, specific structural and functional details disclosed herein should not be construed as limitations, but merely as a representative basis for teaching those skilled in the art how to use the embodiments in various ways. As will be understood by those skilled in the art, various features shown and described with reference to any one of the drawings can be combined with features shown in one or more other drawings to produce embodiments that are not expressly shown or described. The combination of features shown provides a representative embodiment for a typical use. However, various combinations and modifications of features consistent with the teachings of the present disclosure may be desirable for use or implementation.
[0008] Since certain elements and / or conditions may naturally change, this disclosure is not limited to the specific embodiments and methods described below. Furthermore, the terms used herein are used solely for the purpose of describing embodiments of this disclosure and are not intended to limit them in any way.
[0009] When used in the specification and claims, the singular form includes plural subjects unless the context clearly indicates otherwise. For example, a reference to a singular element is intended to include multiple elements.
[0010] A description of a group or classification of materials suitable for a given purpose in relation to one or more embodiments suggests that any mixture of any two or more components of that group or classification is suitable. A description of components in chemical terms does not necessarily exclude chemical interactions among the components of a mixture once it has been mixed, with respect to the components at the time of addition to any combination specified in the description.
[0011] Unless expressly indicated otherwise, all numerical quantities in this description indicating dimensions or material properties should be understood to be modified by the word "approximately" when describing the broadest scope of this disclosure.
[0012] The first definition of an acronym or other abbreviation applies to all subsequent uses of the same abbreviation in this application and, by extension, to the ordinary grammatical variations of the abbreviation initially defined. Unless otherwise stated, the measurement of a characteristic is identified by the same art referred to earlier or later with respect to the same characteristic.
[0013] The phrase “substantially” may be used in this application to describe embodiments disclosed or claimed. The phrase “substantially” may modify any value or related feature disclosed or claimed in this disclosure. “Substantially” may mean that the value or related feature it modifies is within ±0%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, or 10% of that value or related feature.
[0014] Reference is made in detail to the compositions, embodiments, and methods of the embodiments known to the inventors. However, the disclosed embodiments are merely illustrative of the present disclosure, which may be embodied in various and alternative forms. Accordingly, the specific details disclosed herein should not be construed as limiting, but rather should be construed as merely a representative basis for teaching those skilled in the art to variously employ the present disclosure.
[0015] Due to rising carbon dioxide emissions and the relatively high dependence on non-renewable fossil fuels as energy carriers in the transportation sector, there is an ever-increasing need to develop and commercialize transportation technologies that use clean and sustainable energy sources. One promising technology is fuel cells. Fuel cells use oxygen from air and compressed hydrogen fuel as a fuel source, while emitting only water and heat. Widespread adoption of fuel cells may reduce carbon dioxide emissions. However, widespread adoption requires further technological development. One area of further technological development is improving the durability of catalyst materials in fuel cells.
[0016] Figure 1 schematically illustrates a side view of a fuel cell 10. The fuel cells 10 can be stacked to create a fuel cell stack. The fuel cell 10 includes a polymer electrolyte membrane (PEM) 12, an anode 14, a cathode 16, and first and second gas diffusion layers (GDL) 18 and 20. The PEM 12 is disposed between the anode 14 and the cathode 16. The anode 14 is disposed between the first GDL 18 and the PEM 12, and the cathode 16 is disposed between the second GDL 20 and the PEM 12. The PEM 12, the anode 14, the cathode 16, and the first and second GDLs 18 and 20 include a membrane electrode assembly (MEA) 22. First and second sides 24 and 26 of the MEA 22 are coupled by flow fields 28 and 30, respectively. The flow field 28 supplies hydrogen fuel, such as H2, to the MEA 22, as indicated by arrow 32. The flow field 30 supplies O2 to the MEA 22, as indicated by arrow 34. A catalytic material, such as platinum, is used at the anode 14 and the cathode 16. The catalytic material is generally the most expensive component of the MEA 22.
[0017] At the anode 14, the catalytic material (e.g., platinum, Pt) catalyzes the hydrogen oxidation reaction (HOR) (e.g., H2→2H + +2e - ), which creates a flow of electrons through a conductor path 36 (e.g., a wire). At the cathode 16, the catalytic material catalyzes the oxygen reduction reaction (ORR) (1 / 2O2+2H + +2e - →H2O), where electrons are supplied from the conductor path 36. H2O and heat from the ORR exit the fuel cell 10 through the second flow field 30, as indicated by arrow 38. The loading of the catalytic material at the cathode 16 is higher than the loading at the anode 14, because the ORR reaction kinetics are significantly slower than the HOR reaction. A loading as low as 0.025 mgPt / cm 2 for the anode 14 may result in a reaction loss of 20 mV or less for the HOR. A loading of 0.1, 0.2, 0.3, or 0.4 mgPt / cm 2The loading amount of cathode 16 can result in reaction losses of 400mV or more.
[0018] During the operation of the fuel cell 10, the catalyst material degrades at the anode 14 and cathode 16, which can lead to an increase in the reaction overpotential that develops in the fuel cell 10 over time. Various phenomena can cause the degradation of the catalyst material in the fuel cell. Fluctuations in the amount of catalyst loaded at the cathode 16 during the operation of the fuel cell 10 can lead to changes in the cathode potential, for example, changes within one or a range of the following values: 0.7, 0.8, 0.9, and 0.95 V. Changes in the cathode potential at this level can lead to the degradation of the catalyst material at the cathode 16. The effects of starting and stopping, or the effects of localized fuel depletion, can lead to the degradation of the catalyst material at the anode 14. Since a substantial reduction in the amount of catalyst material loaded can significantly help to achieve the cost target of the fuel cell 10, identifying systems, structures, and methods for reducing the degradation of the catalyst material will help to satisfy the beginning-of-life (BOL) and end-of-life (EOL) performance indicators.
[0019] According to one proposal, carbon-encapsulated platinum nanoparticles can be used as a catalyst material for PEM fuel cells. Platinum nanoparticles can be co-synthesized using a combination of aniline and H2PtCl6·6H2O hydrated salts and carbon nanofibers (CNF), resulting in a platinum nanoparticle catalyst encapsulated by a relatively thin carbon layer attached to the CNF surface. The chemical reactions that form the encapsulation structure, the chemical structure of the encapsulation shell, and the protective mechanism are not disclosed or proposed in this proposal.
[0020] What is needed are defective carbon-based coating compositions and methods for forming such compositions using precursor metal salts and precursor carbon to improve the performance of PEM fuel cells by reducing the degradation of catalyst materials and helping to satisfy BOL and EOL performance indicators. Aspects of this disclosure are directed toward discovering chemical reactions between precursor metal salts and precursor carbon using first-principles density functional theory (DFT) and / or abu initio molecular dynamics (AIMD) algorithms, calculations and / or methods to yield such defective carbon-based coating compositions.
[0021] Algorithms, calculations, and / or methods of DFT and / or AIMD of one or more embodiments are implemented using a computer platform, for example, the computing platform 50 shown in Figure 2. The computing platform 50 may include a processor 52, memory 54, and non-volatile storage 56. The processor 52 may include one or more devices selected from a high-performance computing (HPC) system, including high-performance cores, microprocessors, microcontrollers, digital signal processors, microcomputers, central processing units, field-programmable gate arrays, programmable logic devices, state machines, logic circuits, analog circuits, digital circuits, or other devices that process signals (analog or digital) based on computer-executable instructions located in memory 54. The memory 54 may include, but is not limited to, a single memory device or several memory devices, including random access memory (RAM), volatile memory, non-volatile memory, static random access memory (SRAM), dynamic random access memory (DRAM), flash memory, cache memory, or any other device capable of storing information. Non-volatile storage 56 may include one or more persistent data storage devices, such as hard drives, optical drives, tape drives, non-volatile solid-state devices, cloud storage, or any other devices capable of permanently storing information.
[0022] The processor 52 may be loaded into memory 54 and configured to execute computer-executable instructions that reside in a DFT / AIMD software module 58 in non-volatile storage 56 and embody one or more embodiments of DFT / AIMD algorithms, calculations and / or methods. The software module 58 may include an operating system and applications. The software module 58 may be compiled or translated from computer programs created using a variety of programming languages and / or technologies, including, but not limited to, Java, C, C++, C#, Objective-C, Fortran, Pascal, JavaScript, Python, Perl, and PL / SQL, either alone or in combination.
[0023] When executed by processor 52, computer-executable instructions of the DFT and / or AIMD software module 58 can cause the computing platform 50 to implement one or more DFT and / or AIMD algorithms and / or methods disclosed herein. Non-volatile storage 56 may also include DFT / AIMD data 60 supporting the functions, features, calculations and methods of one or more embodiments described herein.
[0024] Program code embodying the algorithms and / or methods described herein may be distributed individually or collectively as program products in various different forms. Such program code may be distributed using a computer-readable storage medium having computer-readable program instructions for causing a processor to implement aspects of one or more embodiments. A computer-readable storage medium, which is essentially non-temporary, may include volatile and non-volatile, removable and non-removable tangible media implemented in any method or technique for storing information, e.g., computer-readable instructions, data structures, program modules, or other data. A computer-readable storage medium may further include RAM, ROM, erasable programmable read-only memory (EPROM), electro-erasable programmable read-only memory (EEPROM), flash memory, or other solid-state memory technologies, portable compact disk read-only memory (CD-ROM), or other optical storage, magnetic cassettes, magnetic tapes, magnetic disk storage, or other magnetic storage devices, or any other medium that can be used to store desired information and can be read by a computer. Computer-readable program instructions can be downloaded over a network to a computer, another type of programmable data processing device, or other device from a computer-readable storage medium, or to an external computer or external storage device.
[0025] A computer, another type of programmable data processing device, or another device can be instructed to function in a particular manner to produce a product that includes instructions that perform functions, actions, and / or operations specified in a flowchart or diagram, using computer-readable program instructions stored in a computer-readable medium. In certain alternative embodiments, the functions, actions, and / or operations specified in a flowchart or diagram can be reordered, processed sequentially, and / or simultaneously in conjunction with one or more embodiments. Furthermore, any flowchart and / or diagram, in conjunction with one or more embodiments, may contain more or fewer nodes or blocks than those shown.
[0026] In one or more embodiments, DFT and / or AIMD algorithms, calculations and / or methods demonstrate that specific chemical reactions between a metal salt of a precursor and carbon molecules of a precursor result in defective carbon-based coating compositions. These compositions can be used as catalysts in the cathode and / or anode of a fuel cell to provide a cost-effective protective mechanism for the catalyst material and improve the operating life of the catalyst material. The DFT and / or AIMD algorithms, calculations and / or methods show that Pt-Pt bonds are present as a portion of the catalyst material formed from the precursor, and Pt-C bonds are present between the defective carbon-based coating composition and the catalyst material. The DFT and / or AIMD algorithms, calculations and / or methods further demonstrate that the defective carbon-based coating compositions can be doped by adding dopants to the chemical reaction as reactants. As shown herein, dopants can promote better bonding between the defective carbon-based coating composition and the catalyst material, thereby enhancing the electrode catalyst performance of a fuel cell using the catalyst material and the defective carbon-based coating composition. In one or more embodiments, doping with n-type nitrogen (N) and p-type boron (B) can promote stronger bonding of the defective carbon-based coating composition to the catalyst material, further demonstrating that doping can positively affect the interface between the catalyst material and carbon in the carbon network. In one or more embodiments, several precursor carbon molecules are disclosed that can participate in the reaction of the precursor to result in a defective carbon-based coating composition. The precursor carbon molecules may be non-aromatic. The precursor carbon molecules may be chitosan, metal-organic frameworks (MOFs), sugars or cellulose molecules, or ionic liquids. The catalyst material may be platinum. The catalyst material may be a nanoscale catalyst material.
[0027] In one embodiment, a fuel cell catalyst material at least partially coated with a defective carbon-based coating material can be formed by a chemical reaction between H₂PtCl₆·6H₂O as a precursor metal salt and aniline as a precursor carbon molecule. During the chemical reaction of this set of precursors, a Pt-aniline complex may be formed. When the surface of a catalyst support (e.g., carbon nanofibers) is coated with the Pt-aniline complex and subsequently annealed at 600 to 900°C in a nitrogen (N₂) atmosphere, a relatively thin, defective carbon-based coating material is formed from the precursor carbon molecules on the surface of platinum nanoparticles. In one embodiment, ab initio molecular dynamics (AIMD) is used to identify the types of chemical reactions that occur during the annealing process and to identify the nanostructures formed after such chemical reactions.
[0028] Simulations of AIMD molecular dynamics methods that use first-principles calculations, such as DFT, can be used to calculate interatomic forces at each atom within a molecule. Correspondingly, AIMD can be used to create a hypothetical atomic-scale chemical reactor containing chemical precursors that are simulated at relatively high temperatures, and the chemical reactions that occur between the precursors within the AIMD hypothetical atomic-scale chemical reactor can be observed. Regarding this chemical reaction, the H₂PtCl₆·6H₂O hydrate salt first forms PtCl₆ in an aqueous environment 2- dissociates into anions and H₃O + cations. Accordingly, three PtCl₆ 2- anions, six H₃O +By placing a cation, 12 H2O molecules, 12 aniline molecules, and 10 N2 molecules within a virtual atomic-scale chemical reactor (a periodic cube with fixed side lengths (e.g., 15 Å)), the total number of atoms becomes 269. Given the relatively large number of atoms in the virtual atomic-scale chemical reactor, the AMD simulation is run at an elevated temperature (e.g., 2000 K), higher than the actual physical annealing temperature (e.g., 900 °C). In one embodiment, using these precursors placed within the virtual atomic-scale chemical reactor (high density, with intermolecular distances between molecules (e.g., greater than a certain value (e.g., 2 Å)), and having various random initial positions and molecular orientations), four different AIMD simulations were run for a predetermined amount of simulation time to observe the graphitization reaction (i.e., formation of CC bonds) as well as the formation of Pt-C bonds. The simulation time for a predetermined quantity may be any of the following values, or any two of the following ranges: 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, and 50 picoseconds (ps).
[0029] Figure 3 is a schematic diagram illustrating the formation of a Pt-C bond from an AIMD simulation of the chemical reaction between Pt hydrate salt in water and aniline after the annealing process under an inert N2 atmosphere. The dotted box 62 shows three PtCl6 atoms placed in a hypothetical atomic-scale chemical reactor. 2- Anions, six H3O +The diagram illustrates a cation, 12 H2O molecules, 12 aniline molecules, and 10 N2 molecules. Arrow 64 indicates an AIMD simulation of the chemical reaction between Pt hydrate salt in water and aniline after the annealing process under an inert N2 atmosphere. Dotted box 66 illustrates the ring-to-ring formation of the two aniline groups. Dotted box 68 illustrates the ring-opening of aniline and attachment to a complete aniline ring. Dotted box 70 illustrates the ring-opening of aniline and attachment to the Pt atom. The concentration of ring-to-ring bond formation is governed by three different molecules shown in dotted boxes 66, 68, and 70. According to one AIMD simulation, approximately 33% of aniline molecules form the ring-to-ring bond shown in box 66, less than 16% of aniline molecules form the ring-to-chain bond shown in box 68, and less than 3% of aniline molecules form the chain-to-platinum bond in box 70. The aforementioned AIMD simulation was performed at a relatively high temperature of 2000K, significantly higher than the processing temperature in typical experiments. Therefore, the concentrations determined in the molecules reacted using the AIMD simulation may not match those achieved experimentally.
[0030] In one or more embodiments, the formation of the resulting Pt nanoparticles follows processing conditions similar to those illustrated in Figure 3. The carbon molecules form a matrix of angstrom-sized nanopores due to the formation of ring-to-ring bonds, which can be separated by a relatively small number of carbon atom chains formed from the ring-opening reaction. The angstrom-sized nanopores may be any of the following values, or any two of the following ranges: 0.5, 1, 2, 3, 4, 6, 8, 10, and 12 angstroms. The relatively small number of carbon atom chains may be 2, 3, 4, 5, and 6. Some of the relatively small number of carbon atom chains can also form Pt-C bonds together with the catalyst nanoparticles. By implementing the defective carbon-based coating compositions of one or more embodiments, the following advantages can be achieved: (1) Minimal mass transport obstacles for thin carbon encapsulation (O2, H3O +(1) H2 and other hydrogen fuels can pass through the atomically porous structure, (2) the formation of Pt nanoparticle aggregates in PEM fuel cells (which reduces catalytic activity) is reduced, resulting in a significantly smaller decrease in the performance of the PEM fuel cell after 30,000 cycles of operation, (3) atomic porosity may reduce the ability of the sulfonic acid groups of the ionomer in the PEM fuel cell to directly adhere to the surface of the catalyst nanoparticles (which can cause loss of catalytic activity), and / or (4) reduce the elution of Pt from the surface of the catalyst nanoparticles.
[0031] Figure 4 illustrates a schematic diagram of a defective carbon-based coating composition 72 that at least partially coats the surface of the catalyst material 74. In one or more embodiments, the carbon-based coating composition is an incomplete multilayer three-dimensional carbon structure having aromatic cyclic carbon groups. Its thickness may range from two to three layers of graphene-like material to about 1 nanometer thick. In other embodiments, the carbon-based coating composition may be relatively two-dimensional. The carbon-based coating composition may have sp2 carbon structures and / or graphite-like structures. In one embodiment, the carbon-based coating composition has 75% or more sp2 hybridization. In other embodiments, the sp2 hybridization may be 25% or 50% or more. The defective carbon-based coating composition may include carbon networks 75 and atomic defects 77. The catalyst material 74 may be nano-sized platinum, platinum-cobalt, platinum-nickel, or any other metal nanostructure catalyst material. The catalyst material 74 is supported on a catalyst support 76. In one or more embodiments, the defective carbon-based coating composition 72 is doped with one or more dopants. As shown in Figure 4, the defective carbon-based coating composition 72 is doped with nitrogen (N), i.e., n-type doping in graphene. N doping can promote stronger bonding of the defective carbon-based coating composition 72 to the surface of the catalyst material 74. In one or more embodiments, the defective carbon-based coating composition 72 may be doped with boron, i.e., a p-type dopant, in addition to or instead of N doping. The thickness of the defective carbon-based coating composition 72 may be any of the following values, or any two of the following ranges: 0.1, 0.5, 0.6, 0.7, 0.8, 0.9, and 1.0 nanometers. In other embodiments, one or more layers of a defective graphene coating may be any of the following values, or any two of the following ranges: 0.2, 0.3, 0.6, 0.9, 1.2, 1.5, 1.8, 2.1, 2.4, 2.7, and 3 nanometers, where the interlayer distance between two graphene sheets (e.g., in graphite) is approximately 0.3 nanometers, which may increase or decrease depending on the dopant, pillar agent, or oxygen functional group.For example, the interlayer distance of graphene oxide (GO) having many oxygen functional groups may be about 0.85 nanometers. In other embodiments, hydrated cations, such as Li, are used. + na + and K + Ions can change the interlayer distance of graphene to approximately 0.935, 0.896, and 0.882 nanometers, respectively.
[0032] As shown in Figure 4, the defective carbon-based coating composition 72 contains several atomic defects 77. The size of the atomic defects may be any of the following values or any two of the following ranges: 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 1.0 nanometers. In other embodiments, one or more layers of the defective graphene coating may be any of the following values or any two of the following ranges: 0.2, 0.3, 0.6, 0.9, 1.2, 1.5, 1.8, 2.1, 2.4, 2.7, and 3 nanometers, where the interlayer distance between two graphene sheets (e.g., in graphite) is approximately 0.3 nanometers, which may increase or decrease depending on the dopant, pillar agent, and oxygen functional group. The size of the atomic defects can be controlled based on the type of hydrocarbon molecule of the precursor used. In certain embodiments, the size of the atomic defects may be the size of the number of carbon vacancies due to the defects. The number of carbon vacancies may be any of the following values or any two of the following ranges: 1, 2, 3, 4, 5, and 6 carbon vacancies. The carbon vacancies may be the result of the unwinding of aromatic rings in the precursor hydrocarbon molecules. The defects may be graphene-based defects disclosed in U.S. Patent Applications No. 16 / 544511 and 16 / 694305, which are included in their entirety by reference herein.
[0033] The DFT and / or AIMD algorithms, calculations, and / or methods demonstrate the interaction between the defective carbon-based coating composition 72 and the catalyst material 74. Using the DFT and / or AIMD algorithms, calculations, and / or methods, a chemical interface between a pure graphene sheet 78 and Pt atoms 80 was constructed, as shown in Figure 5A. Using the DFT and / or AIMD algorithms, calculations, and / or methods, a chemical interface between a B-doped graphene sheet 82 and Pt atoms 80 was constructed, as shown in Figure 5B, and a chemical interface between an N-doped graphene sheet 84 and Pt atoms 80, as shown in Figure 5C. Table 1 contains the DFT binding energies between Pt atoms 80 and the doped graphene sheets 82 and 84 relative to the pure graphene sheet 78. As shown in Table 1, the binding energies become more negative when graphene is doped with B and / or N.
[0034] [Table 1]
[0035] It is not expected that p-type B doping and n-type N doping in graphene can contribute to Pt binding, because B doping and N doping in graphene should lead to opposite effects (i.e., electron donation and electron extraction).
[0036] Figure 6A is a schematic diagram of an isosurface plot 86 of the simulated electron density difference at the chemical interface between a B-doped graphene sheet 82 and a Pt atom 80. Figure 6B is a schematic diagram of an isosurface plot 88 of the simulated electron density difference at the chemical interface between an N-doped graphene sheet 84 and a Pt atom 80.
[0037] The first and second shaded regions 90 and 92 correspond to the electron storage region and the electron depletion region, respectively (±0.003 e·Å). 3). In the case of B-doping shown in Figure 6A, it is observed that Pt forms chemical bonds with both boron and carbon (B-Pt-C type bonds). In contrast, as shown in Figure 6B, Pt readily forms chemical bonds away from nitrogen (C-Pt-C type bonds). In the case of pure graphene, as shown in Figure 5A, Pt simply forms a single bond with carbon (Pt-C bond). Thus, the formation of two single bonds with Pt in the doped graphene system partially explains the more favorable bonding between the Pt atom and the doped graphene system. Furthermore, in Figure 6A, it is observed that B-doped graphene has more electron depletion regions on boron compared to nitrogen (second shaded region 92), and exhibits more electron storage around nitrogen in nitrogen-doped graphene. This first explains that doping with B and N leads to opposite effects, for example, electron extraction rather than electron donation. However, the Pt atoms tend to move away from the nitrogen atoms, forming chemical bonds with two adjacent carbon atoms, which also significantly affects the relative bond energy by about 0.5 eV. However, adding boron instead of nitrogen can also significantly affect the relative bond energy, as Pt has an affinity to bond directly to the boron atoms (the relative bond energy is affected by about 0.8 eV). In one embodiment, both electron-donating and electron-extracting dopants in graphene can directly assist the bonding of Pt either by making the Pt bond stronger (e.g., p-type B doping) or by influencing the nearest adjacent carbon atom located next to the dopant (e.g., n-type N doping).
[0038] Based on our findings above using H2PtCl6·6H2O as the precursor metal salt and aniline as the precursor hydrocarbon molecule, the main chemical reaction involved in the formation of the defective carbon-based coating composition is the formation of a CC bond between the CH moieties of two aniline molecules. In one or more embodiments, precursor carbon molecules having aromatic cyclic groups produce a defective carbon-based coating composition similar to one shown in Figure 4. In one or more embodiments, one or more of N, B, S, P, O, Si, and Al atoms, and combinations thereof, can be doped into the defective carbon-based coating composition to further improve the electrode catalytic properties of the Pt-C bond and / or PEM fuel cell. As shown, Cl atoms are not typically incorporated into the defective carbon-based coating composition. Therefore, in one or more embodiments, platinum-based salts other than H2PtCl6·6H2O can be used as the precursor metal salt. Other, not limited to, examples of platinum salts include PtCl n Or Pt(NH3)2Cl n (n=2~4) is included. The use of platinum salts containing N may be beneficial to increase the amount of N doped into the carbon network. Alternative aromatic cyclic groups that can be used as precursor carbon molecules for producing defective carbon-based coated compositions are disclosed in U.S. Patent Application No. 16 / 833039, which is incorporated herein by reference in its entirety.
[0039] In addition to aromatic cyclic carbon precursors, in one or more embodiments, non-aromatic carbon molecules can be used as precursor carbon molecules to produce carbon-based coating compositions with defects similar to those described above. In one embodiment, the non-aromatic carbon molecule may be chitosan. In another embodiment, the non-aromatic carbon molecule may be a MOF. In yet another embodiment, the non-aromatic carbon molecule may be a sugar or cellulose molecule. In yet another embodiment, the non-aromatic carbon molecule may be an ionic liquid.
[0040] Referring to Figure 1, in one or more embodiments, fuel cell catalyst materials having a defective carbon-based coating are disclosed, which are constructed by controlling the atomic and molecular interfaces between the defective carbon-based coating and the catalyst material. The defective carbon-based coating composition provides relatively long-term stability to the PEM fuel cell by being configured to suppress metal leaching of Pt and Pt alloy catalysts in the PEM fuel cell environment.
[0041] In one or more embodiments, catalyst materials for fuel cells are disclosed. The catalyst material for fuel cells comprises metal catalyst particles formed from a metallic material. The average diameter of the metallic material can be nanoscale. The metallic material includes, or can be formed entirely from, pure Pt, Pt-M alloys (M=Co, Ni, or other metals from the periodic table), other platinum group (PGM) metals (e.g., Ru, Rh, Pd, Os, Ir), PGM-M (or Pt-PGM-M) alloy systems, non-PGM catalyst materials, and combinations thereof.
[0042] The catalyst material for the fuel cell may further include a carbon-based coating composition that at least partially (or completely) coats at least some of the metal catalyst particles. The defective carbon-based coating composition may include a carbon network. The carbon-based coating composition can be doped with a dopant. Not limited examples of dopants include N, B, P, S, O, Si, Al, Cl, and / or F atoms. The atoms of the dopant can be bonded within the carbon network or physically positioned on the carbon-based coating. The thickness of the defective carbon-based coating composition may be any of the following values or any two of the following ranges: 0.2, 0.5, 0.75, 1.0, 1.25, 1.5, 1.75, and 2.0 nanometers. In other embodiments, one or more layers of the defective graphene coating may be any of the following values, or any two of the following ranges: 0.2, 0.3, 0.6, 0.9, 1.2, 1.5, 1.8, 2.1, 2.4, 2.7, and 3 nanometers, where the interlayer distance between two graphene sheets (e.g., in graphite) is approximately 0.3 nanometers, which may increase or decrease depending on the dopant, pillar agent, and oxygen functional group. Their thicknesses can result in acceptable mass transport of species involved in the ORR catalytic reaction. The catalytic material may be configured to mitigate the degradation of the catalytic material atoms. Reducing catalyst degradation can have one or more of the following advantages: (1) reducing the loss of electrochemically active surface area (ECSA), (2) preventing the movement of catalyst ions to or into the interface between the polymer electrolyte membrane (PEM) and the catalyst layer, and / or (3) preventing the aggregation of catalyst nanoparticles through immobilization provided by graphite sealing, thus potentially suppressing PEM degradation. The addition of the defective carbon-based coating composition improves the bonding between the defective carbon-based coating composition and the metal catalyst particles, as well as allowing H2O, O2, and H3O to enter through the defect sites. + It can influence and / or enhance the transport of the underlying material.
[0043] Part or all of the graphene-based coating composition can be in direct contact with metal catalyst particles in the catalyst layer (i.e., the anode and / or cathode catalyst layer). Part or all of the carbon-based coating composition can be loosely bonded to the metal catalyst particles at a specific average distance. The average distance of the layer closest to the particles may be one of the following values, or any two of the following ranges: 0.2, 0.5, 0.75, 1.0, 1.25, 1.5, 1.75, and 2.0 nanometers.
[0044] The carbon-based coating composition may contain several defects configured to capture eluted metal species of catalyst particles, which are ionized from the atomic form of the catalyst particles. The captured catalyst particles (e.g., Pt catalyst particles) can still act as a catalyst because they are in contact with a conductor (i.e., the defective carbon-based coating composition). The loss of electrochemical active surface area (ECSA) is reduced as fewer catalyst particles can migrate toward the PEM. Since there is less redeposition of catalyst particles onto the PEM, this can potentially lead to less PEM degradation. Preventing ECSA loss and PEM degradation can improve the lifespan of the PEM fuel cell. During negative sweeping, the catalyst material on the defects can be ionized and released, and redeposited within the catalyst layer.
[0045] The defective carbon-based coating composition may be configured to prevent aggregation of catalyst particles through fixation. The defective carbon-based coating composition may be configured to allow transport of H2 and / or other reactants / products of the fuel cell, depending on the operating voltage of the PEM fuel cell.
[0046] The defective carbon-based coating composition may also contain oxygen functional groups, such as epoxy (-O-), carbonyl (=O), carboxyl (-COOH), and / or hydroxyl (-OH). The oxygen functional groups can optimize the transport and diffusion of Pt, H2, other hydrogen fuels, O2, and H2O. The defective carbon-based coating composition may also contain nitrogen functional groups (such as -NH2), sulfur functional groups (such as -SH), phosphorus functional groups (such as -PH3), and / or boron functional groups (such as -BH2). In other embodiments, combinations of these dopants can also be used simultaneously. Carbon rings, which may have 4 to 12 carbon atoms (but typically 6), can be linearly attached to a one-dimensional chain, or attached to each other as in graphene, or linked via linker atoms (e.g., B, P, S, N) or some of the above combinations.
[0047] One or more fuel cell catalyst materials of an embodiment can be mixed with commercially available catalyst materials (e.g., unmodified catalyst materials). For example, pure Pt and / or Pt alloys (Pt-Ni, Pt-Co) can be used at the anode, and the fuel cell catalyst of the one or more embodiments can be used at the cathode. In other embodiments, either the anode or the cathode can use the fuel cell catalyst material of the one or more embodiments in part with a commercially available catalyst material. For example, in a given catalyst electrode material, 5 to 50% of the Pt and / or Pt alloy catalyst can be modified with a graphene coating. In other embodiments, more than 50 to 75% of the catalyst material can be modified with a graphene coating, where the remaining material is a commercially available material.
[0048] The fuel cell catalysts of one or more embodiments described above can be formed by reacting a precursor Pt salt with a precursor carbon molecule. The precursor metal salts are H2PtCl6·6H2O and PtCl n , or Pt(NH3)2Cl n[wherein n=2 to 4]. The precursor carbon molecule may be a non-aromatic carbon molecule. Not limited examples of the precursor carbon molecule may include chitosan, MOF structures, sugar or cellulose molecules, or ionic liquids. The reaction forms a catalytic material comprising metal catalyst particles and a defective carbon-based coating composition that at least partially coats at least some of the metal catalyst particles. In such embodiments, the coating of the carbon-based composition is formed during the synthesis of the metal catalyst particles. In other embodiments, the coating of the carbon-based composition is formed after the synthesis of the metal catalyst particles that form part of the anode and / or cathode layer. Methods for forming the catalytic material can include annealing processes, ion bombardment, solid-phase processes, solvent-based methods, and / or deposition techniques. Following these techniques, a secondary heat treatment may be carried out in the presence of oxidizing and / or reducing agents, such as air, O2, N2, Ar, H2, other gases, and mixtures thereof.
[0049] In another embodiment, the defective carbon-based coating composition can also prevent the elution of catalyst atoms and / or aggregation of catalyst nanoparticles for other non-PGM catalyst nanoparticles. To achieve this objective, the Pt salt precursor used for co-synthesis can be replaced with the M salt precursor required for the synthesis of non-PGM catalyst nanoparticles.
[0050] The fuel cell catalyst materials of one or more embodiments described above can be co-synthesized simultaneously. Coated catalyst particles can be synthesized independently or in an environment having a catalyst support for connecting the coated catalyst particles. The catalyst support may be a carbon support. The carbon support can be formed from nanowires (e.g., carbon nanotubes, vanadium nitride (VN), and combinations thereof), fine particles (e.g., micro-sized high-surface-area carbon particles), solid surfaces, and combinations thereof.
[0051] While exemplary embodiments have been described above, it is not intended that these embodiments describe all possible forms that would be covered by the claims. The language used in the specification is descriptive, not restrictive, and it should be understood that various modifications can be made without departing from the spirit and scope of this disclosure. As stated above, features of various embodiments can be combined to form further embodiments of this disclosure that are not expressly described or described. Various embodiments may be described as offering advantages or being preferable to other embodiments or practices of the prior art with respect to one or more desirable features, but those skilled in the art will recognize that one or more features may be compromised to achieve desired characteristics of the overall system depending on the particular use and implementation. Those characteristics may include, but are not limited to, cost, strength, durability, life cycle cost, marketability, appearance, packaging, size, utility, weight, manufacturability, ease of assembly, etc. Thus, as long as an embodiment is described as being less desirable than other embodiments or practices of the prior art with respect to one or more features, those embodiments may not be outside the scope of the disclosure and may be desirable for a particular use.
Claims
1. Metal catalyst particles formed from a metal material, A carbon-based coating composition that at least partially coats at least some of the metal catalyst particles. and The carbon-based coating composition includes a carbon network, The carbon-based coating composition is doped with a dopant. The carbon-based coating composition includes several defects formed by one or more carbon atom vacancies in the carbon network, The carbon-based coating composition is derived from non-aromatic carbon molecules selected from the group consisting of chitosan, metal-organic frameworks (MOFs), sugars, cellulose molecules, and ionic liquids. The thickness of the carbon-based coating composition is 0.2 to 3.0 nanometers. and, The coating of the metal catalyst particles is formed by reacting a metal-containing precursor metal salt with the precursor of the non-aromatic carbon molecule. Fuel cell catalyst materials.
2. The fuel cell catalyst material according to claim 1, wherein the metallic material is a pure Pt, Pt-M alloy, and M is a metal, another platinum group element, a PGM-M alloy system, a non-PGM catalyst material, and a combination thereof.
3. The fuel cell catalyst material according to claim 1, wherein the dopant comprises N, B, P, S, O, Si, Al, Cl and / or F atoms.
4. Catalyst support, and A catalyst material supported on the catalyst carrier, comprising metal catalyst particles formed of a metal material and a carbon-based coating composition that at least partially coats at least some of the metal catalyst particles. Includes, The carbon-based coating composition includes a carbon network, The carbon-based coating composition is doped with a dopant. The carbon-based coating composition includes several defects formed by one or more carbon atom vacancies in the carbon network, The carbon-based coating composition is derived from non-aromatic carbon molecules selected from the group consisting of chitosan, metal-organic frameworks (MOFs), sugars, cellulose molecules, and ionic liquids. The thickness of the carbon-based coating composition is 0.2 to 3.0 nanometers. and, The coating of the metal catalyst particles is formed by reacting a metal-containing precursor metal salt with the precursor of the non-aromatic carbon molecule. Fuel cell catalyst electrode.
5. The fuel cell catalyst electrode according to claim 4, wherein the metallic material is a pure Pt, Pt-M alloy, and M is a metal, another platinum group element, a PGM-M alloy system, a non-PGM catalyst material, and a combination thereof.
6. The fuel cell catalyst electrode according to claim 4, wherein the dopant comprises N, B, P, S, O, Si, Al, Cl and / or F atoms.
7. A method for producing a fuel cell catalyst material according to Claim 1, A step of reacting a metal salt of a metal-containing precursor with carbon molecules of the precursor to form a catalyst material comprising metal catalyst particles and a carbon-based coating composition that at least partially coats at least some of the metal catalyst particles. The method comprising, wherein the carbon molecule of the precursor is a non-aromatic carbon molecule selected from the group consisting of chitosan, metal-organic frameworks (MOFs), sugars, cellulose molecules, and ionic liquids.
8. The metal salt of the precursor is H 2 PtCl 6 6H 2 O, PtCl n or Pt(NH 3 ) 2 Cl n The method according to claim 7, wherein [wherein 2 ≤ n ≤ 4].
9. The method according to claim 7, wherein the thickness of the carbon-based coating composition is 0.2 to 3.0 nanometers.
Citation Information
Patent Citations
Self-supported PtCo alloy nanoparticle catalyst and preparation method and application thereof
CN108736031A
MOFs-derived porous carbon-coated NiFe nano-alloy oxygen evolution catalyst and preparation method thereof
CN111477883A